Pernio-like lesions and coagulopathy in a patient with COVID-19 infection (2020)
Pernio-like lesions, or ‘COVID-toes’, have recently been reported around the world (1- 3). The etiology and optimal management remain largely unknown. We present the case of a patient with COVID-toes in association with acute SARS-CoV-2 infection, in whom a comprehensive hematologic workup revealed a striking elevation of factor VIII activity and vWF level, suggesting that endothelial dysfunction may be associated with this cutaneous manifestation of coronavirus infection.